2018
DOI: 10.1002/jbio.201700370
|View full text |Cite
|
Sign up to set email alerts
|

Pain management using photobiomodulation: Mechanisms, location, and repeatability quantified by pain threshold and neural biomarkers in mice

Abstract: Photobiomodulation (PBM) is a simple, efficient and cost-effective treatment for both acute and chronic pain. We previously showed that PBM applied to the mouse head inhibited nociception in the foot. Nevertheless, the optimum parameters, location for irradiation, duration of the effect and the mechanisms of action remain unclear. In the present study, the pain threshold in the right hind paw of mice was studied, after PBM (810 nm CW laser, spot size 1 or 6 cm , 1.2-36 J/cm ) applied to various anatomical loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 40 publications
0
36
0
1
Order By: Relevance
“…The infrared laser can reduce pain indirectly by modulating the inflammatory process by reducing the concentration of pro-inflammatory cytokines 26) and increasing the levels of anti-inflammatory cytokines 27) . The infrared laser stimulates nociceptors and leads to an increased pain threshold 28) . MTrPs are characterized by muscle fiber shortening, which results in impaired local circulation, leading to poor oxygen and nutrient supply 29) .…”
Section: Discussionmentioning
confidence: 99%
“…The infrared laser can reduce pain indirectly by modulating the inflammatory process by reducing the concentration of pro-inflammatory cytokines 26) and increasing the levels of anti-inflammatory cytokines 27) . The infrared laser stimulates nociceptors and leads to an increased pain threshold 28) . MTrPs are characterized by muscle fiber shortening, which results in impaired local circulation, leading to poor oxygen and nutrient supply 29) .…”
Section: Discussionmentioning
confidence: 99%
“…Of the electrophysical agents, photomodulation has relevance as a complementary treatment for CRPS, where the cellular photobiomodulation (PBMT) effects appear to reverse mitochondrial inhibition, potentiating the effects of sodium–potassium pumps and generating increases in cellular metabolism and proliferation [18]. When adenosine triphosphate is stimulated, peripheral sensitization inhibition occurs, leading to decreases in inflammatory neuropeptides and increases in serotonin and endorphin release [18–20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the increase of the pain threshold in the right hindpaw of mice (measured by von Frey filaments) was demonstrated after photobiomodulation with infrared (810 nm) applied to different anatomical locations. It was also demonstrated that type 1 metabotropic glutamate receptors decreased, and prostatic acid phosphatase and tubulin‐labeled varicosities were increased . Other studies have shown the involvement of the opioid and serotonergic systems in different pain models .…”
Section: Discussionmentioning
confidence: 85%
“…It was also demonstrated that type 1 metabotropic glutamate receptors decreased, and prostatic acid phosphatase and tubulin-labeled varicosities were increased. 59 Other studies have shown the involvement of the opioid and serotonergic systems in different pain models. [60][61][62] However, further investigation is needed to elucidate the specific nuclei and subnuclei of the endogenous pain inhibitory system involved in this antinociceptive phenomenon.…”
Section: Discussionmentioning
confidence: 99%